Recovery and separation of iron from iron ore using innovative fluidized magnetization roasting and magnetic separation - Yu J.; Han Y.; Li Y.; Gao P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this investigation, a pilot-scale fluidized magnetization roasting reactor was introduced and used to enhance magnetic properties of iron ore. Consequently, the effects of roasting temperature, reducing gas CO flow rate, and fluidizing gas N2 flow rate on the magnetization roasting performance were studied. The results indicated that the hematite was almost completely converted into magnetite by a gas mixture of 4 Nm3/h CO and 1 Nm3/h N2 at roasting temperature of 540°C for about 30 s. Under optimized conditions, a high grade concentrate containing 66.84% iron with iron recovery of 91.16% was achieved. The XRD, VSM, and optical microscopy (OM) analyses revealed that most of the hematite, except some coarse grains, was selectively converted to magnetite, and that the magnetic properties were greatly enhanced. Thus, their separation from non-magnetic gangue minerals was facilitated.